Biomechanical characteristics of ligament injuries in the knee joint during impact in the upright position: a finite element analysis - Jia Li; Hanbing Liu; Mingyao Song; Fei Lin; Ziya Zhao; Zhenghui Wang; Liming Hou; Guoan Zhao; Wu Ren (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Background Our study aims to examine stress–strain data of the four major knee ligaments—the anterior cruciate ligament (ACL), the posterior cruciate ligament (PCL), the medial collateral ligament (MCL), and the lateral collateral ligament (LCL)—under transient impacts in various knee joint regions and directions within the static standing position of the human body. Subsequently, we will analyze the varying biomechanical properties of knee ligaments under distinct loading conditions. Methods A 3D simulation model of the human knee joint including bone, meniscus, articular cartilage, ligaments, and other tissues, was reconstructed from MRI images. A vertical load of 300 N was applied to the femur model’s top surface to mimic the static standing position, and a 134 N load was applied to the impacted area of the knee joint. Nine scenarios were created to examine the effects of anterior, posterior, and lateral external forces on the upper, middle, and lower regions of the knee joint. Results The PCL exhibited the highest stress levels among the four ligaments when anterior loads were applied to the upper, middle, and lower parts of the knee, with maximum stresses at the PCL-fibula junction measuring 59.895 MPa, 27.481 MPa, and 28.607 MPa, respectively. Highest stresses on the PCL were observed under posterior loads on the upper, middle, and lower knee areas, with peak stresses of 57.421 MPa, 38.147 MPa, and 26.904 MPa, focusing notably on the PCL-tibia junction. When a lateral load was placed on the upper knee joint, the ACL showed the highest stress 32.102 MPa. Likewise, in a lateral impact on the middle knee joint, the ACL also had the highest stress of 29.544 MPa, with peak force at the ACL-tibia junction each time. In a lateral impact on the lower knee area, the LCL had the highest stress of 22.279 MPa, with the highest force at the LCL-fibula junction. Furthermore, the maximum stress data table indicates that stresses in the ligaments are typically higher when the upper portion of the knee is affected compared to when the middle and lower parts are impacted. Conclusions This study recommends people avoid impacting the upper knee and use the middle and lower parts of the knee effectively against external forces to minimize ligament damage and safeguard the knee.